Evaluation of low-cost computer monitors for the detection of cervical spine injuries in the emergency room: an observer confidence-based study. Issue 11 (20th October 2006) - Brem, M H; Böhner, C; Brenning, A; Gelse, K; Radkow, T; Blanke, M; Schlechtweg, P M; Neumann, G; Wu, I Y; Bautz, W; Hennig, F F; Richter, H
Abstract : Background: To compare the diagnostic value of low-cost computer monitors and a Picture Archiving and Communication System (PACS) workstation for the evaluation of cervical spine fractures in the emergency room. Methods: Two groups of readers blinded to the diagnoses (2 radiologists and 3 orthopaedic surgeons) independently assessed–digital radiographs of the cervical spine (anterior–posterior, oblique and trans-oral-dens views). The radiographs of 57 patients who arrived consecutively to the emergency room in 2004 with clinical suspicion of a cervical spine injury were evaluated. The diagnostic values of these radiographs were scored on a 3-point scale (1 = diagnosis not possible/bad image quality, 2 = diagnosis uncertain, 3 = clear diagnosis of fracture or no fracture) on a PACS workstation and on two different liquid crystal display (LCD) personal computer monitors. The images were randomised to avoid memory effects. We used logistic mixed-effects models to determine the possible effects of monitor type on the evaluation of x ray images. To determine the overall effects of monitor type, this variable was used as a fixed effect, and the image number and reader group (radiologist or orthopaedic surgeon) were used as random effects on display quality. Group-specific effects were examined, with the reader group and additional fixed effects as terms. A significance level of 0.05 was established for assessing the contribution of each fixed effect to the model. Results: Overall, the diagnostic score did not differ significantly between standard personal computer monitors and the PACS workstation (both p values were 0.78). Conclusion: Low-cost LCD personal computer monitors may be useful in establishing a diagnosis of cervical spine fractures in the emergency room.